If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -7 = 14y + 25 Reorder the terms: -7 + 6y = 14y + 25 Reorder the terms: -7 + 6y = 25 + 14y Solving -7 + 6y = 25 + 14y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14y' to each side of the equation. -7 + 6y + -14y = 25 + 14y + -14y Combine like terms: 6y + -14y = -8y -7 + -8y = 25 + 14y + -14y Combine like terms: 14y + -14y = 0 -7 + -8y = 25 + 0 -7 + -8y = 25 Add '7' to each side of the equation. -7 + 7 + -8y = 25 + 7 Combine like terms: -7 + 7 = 0 0 + -8y = 25 + 7 -8y = 25 + 7 Combine like terms: 25 + 7 = 32 -8y = 32 Divide each side by '-8'. y = -4 Simplifying y = -4
| 7-4k=1 | | 6x-9=2x-81 | | 5y=x+20 | | -2(1-2x)-(1-2x)=-x-2 | | -10+8+(-4)= | | 6*(2B-3)=18 | | -14+6x=3 | | lny=2x^2+C | | 4*(5A+1)=24 | | 9x-(3x+11)=43 | | 61-(-23)+21-40= | | 9(4x-3)=50 | | 13-8x=-75 | | 9m-4(2m-4)=12 | | h+1100+l=57400 | | -13+11= | | 2x+50=66 | | 9a+7b=0 | | 2x+50=16 | | 5x-19=-74 | | 3y-5y=50 | | -3(7p+5)-2(5-20p)=3(5+6p) | | 8(x+5)+3=6(x-5) | | x+13=-3 | | 6y-3.2y=7.5 | | (5y+4)-(3+4y)=9 | | -2.7=1.3+0.7x | | 2x+2y-5z=9 | | 16a+2a^4=0 | | -16(x-50)=4(x+5) | | 3x^4+8x^3-7x^2-32x-20=0 | | 2i(3i)= |